IgG4 Related Lung Disorder -A Review - S.Balamithra1 , Brundha M.P.2 , Smiline Girija AS3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
IgG4 disorder is an autoimmune disorder. Its manifestation in the lung causes fibroinflammatory disorder.It is one of the chronic inflammatory disorders. IgG4 is the subclass of IgG. This review is analysed basedon the IgG4 related disorder. Nearly 50 articles were reviewed and this study was conducted for a period ofnearly 15 years.The IgG4 related disorder is a very rare disorder in the world. Moreover, It is an autoimmunedisorder like Systemic lupus erythematosus. It is related to systemic disorder and chronic inflammatorydisorder IgG4 varies high degree of fibrosis and it is prompted by the response of steroid therapy.It is themost common form of immunoglobulin. Ig G also known as secretory immunoglobulin.Ig G4 is a subclassof IgG comprising only 4% in gamma immunoglobulins . IgG4 does not bind to polysaccharides. Increasedlevels of IgG4 in serum usually found in patients suffering sclerosing pancreatitis, cholangitis and interstitialpneumonia caused by the infiltration of IgG4 positive plasma cells. IgG4 has a molecular weight of 159.IgG4 related disorder recognised as one of the rare autoimmune disorders which can affect multiple organsand cause organ failure sometimes. It involves the complement system and interacts with the antibody.Generally IgG4 related disorder is recognised as one of the most rare autoimmune disorders which can affectmultiple organ failure sometimes. It involves complement system and interact with antibody. Generally,IgG4 related disorder most commonly present in in beekeper, animal laboratory workers and individualswho have undergone allergen immunotherapy possess high serum level of IgG4.it is one of the acquiredType II hypersensitivity disorder. This review mainly aims to know the reason behind the clinical lungdisorder.